2013
DOI: 10.1128/jb.00754-13
|View full text |Cite
|
Sign up to set email alerts
|

DNA Uptake by the Nosocomial Pathogen Acinetobacter baumannii Occurs during Movement along Wet Surfaces

Abstract: bThe emergence of Acinetobacter baumannii as an increasingly multidrug-resistant nosocomial pathogen largely relies on acquisition of resistance genes via horizontal gene transfer. Here, we demonstrate that many clinical isolates of A. baumannii take up DNA while they move along wet surfaces. We show that both motility and DNA uptake are abolished after inactivation of pilT, which putatively encodes the type 4 pilus (T4P) retraction ATPase, and comEC, which putatively encodes the DNA uptake channel, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
168
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(172 citation statements)
references
References 55 publications
3
168
1
Order By: Relevance
“…Although bioinformatic studies have identified genes predicted to encode proteins required for the biogenesis of Tfp in A. baumannii, only Acinetobacter nosocomialis strain M2 has been shown conclusively to produce functioning Tfp (66,67), which is glycosylated by a TfpO-like oligosaccharyltransferase (30). Many A. baumannii isolates have been found to be naturally transformable and to exhibit twitching motility (63,(68)(69)(70), two classic Tfp-associated phenotypes, which strongly indicates their presence. Tfp-like structures were also identified on A. baumannii ATCC 17978 (71); furthermore, mutants in predicted Tfp biogenesis components of A. baumannii ATCC 17978 exhibited impaired biofilm formation (71) but the major pilin subunit, PilA, has not been shown to be surface exposed and/or associated with the pilin structures observed.…”
Section: Cell Surfacementioning
confidence: 99%
“…Although bioinformatic studies have identified genes predicted to encode proteins required for the biogenesis of Tfp in A. baumannii, only Acinetobacter nosocomialis strain M2 has been shown conclusively to produce functioning Tfp (66,67), which is glycosylated by a TfpO-like oligosaccharyltransferase (30). Many A. baumannii isolates have been found to be naturally transformable and to exhibit twitching motility (63,(68)(69)(70), two classic Tfp-associated phenotypes, which strongly indicates their presence. Tfp-like structures were also identified on A. baumannii ATCC 17978 (71); furthermore, mutants in predicted Tfp biogenesis components of A. baumannii ATCC 17978 exhibited impaired biofilm formation (71) but the major pilin subunit, PilA, has not been shown to be surface exposed and/or associated with the pilin structures observed.…”
Section: Cell Surfacementioning
confidence: 99%
“…Uptake of free DNA from the medium also is unlikely, although some A. baumannii strains previously were shown to be capable of natural transformation. A. baumannii CIP 70.10 encodes a type IV pilus (T4P) system and a channel formed by the proteins ComA/ComEC implicated in DNA uptake from outside the cell (48). However, transformation efficiency was shown to be very low for strain CIP 70.10 (49).…”
Section: Figmentioning
confidence: 99%
“…For Acinetobacter spp., most of the studies focusing on this issue were performed by using Acinetobacter baylyi strain ADP1 (16)(17)(18)(19)(20), a bacterium not as threatening to human health as A. baumannii (18)(19)(20)(21)(22)(23). Data regarding A. baumannii and competence inducers are scarce (24)(25)(26)(27). Wilharm et al showed previously that several A. baumannii clinical isolates were able to acquire exogenous DNA depending on the expression of pilT, encoding an ATPase involved in type IV pilus retraction, and comEC, encoding the DNA uptake channel (26).…”
mentioning
confidence: 99%
“…Data regarding A. baumannii and competence inducers are scarce (24)(25)(26)(27). Wilharm et al showed previously that several A. baumannii clinical isolates were able to acquire exogenous DNA depending on the expression of pilT, encoding an ATPase involved in type IV pilus retraction, and comEC, encoding the DNA uptake channel (26). Another study showed that the natural competence of Acinetobacter nosocomialis strain M2 relies on the presence of pilA, pilD, and pilT (28).…”
mentioning
confidence: 99%